2012
DOI: 10.1016/j.expneurol.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase overexpression does not modify the disease phenotype of the R6/2 mouse model of Huntington's disease

Abstract: Huntington’s disease (HD) is a devastating autosomal-dominant neurodegenerative disorder initiated by an abnormally expanded polyglutamine in the huntingtin protein. Determining the contribution of specific factors to the pathogenesis of HD should provide rational targets for therapeutic intervention. One suggested contributor is the type 2 transglutaminase (TG2), a multifunctional calcium dependent enzyme. A role for TG2 in HD has been suggested because a polypeptide-bound glutamine is a rate-limiting factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 68 publications
(118 reference statements)
2
6
0
Order By: Relevance
“…Supporting our results, the overexpression of TG2 in R6/2 mice also did not modify the disease phenotype [43], raising additional questions about the role of TG2 activity in HD. The results of our genetic target validation work with a transglutaminase 2 null gene on the background of 2 different mouse models of HD do not support a therapeutic path aimed at TG2 inhibition for the treatment of HD.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Supporting our results, the overexpression of TG2 in R6/2 mice also did not modify the disease phenotype [43], raising additional questions about the role of TG2 activity in HD. The results of our genetic target validation work with a transglutaminase 2 null gene on the background of 2 different mouse models of HD do not support a therapeutic path aimed at TG2 inhibition for the treatment of HD.…”
Section: Discussionsupporting
confidence: 82%
“…In summary, under rigorous experimental conditions we found that the genetic ablation of TG2 does not ameliorate the disease phenotype, including physiological, molecular, neuropathological and behavioral markers in two different HD mouse models. Supporting our results, the overexpression of TG2 in R6/2 mice also did not modify the disease phenotype [43] , raising additional questions about the role of TG2 activity in HD. The results of our genetic target validation work with a transglutaminase 2 null gene on the background of 2 different mouse models of HD do not support a therapeutic path aimed at TG2 inhibition for the treatment of HD.…”
Section: Discussionsupporting
confidence: 82%
“…13 TG2 expression and transglutaminase activity have been shown to be increased in the brains of HD patients, 14 and in vitro and in vivo models have implicated TG2 in HD pathophysiology, 15−18 although more recent contradictory animal data have appeared. 19 The subject of irreversible inhibitors of TG2 has been recently reviewed. 20 Our studies have focused on irreversible inhibitors bearing an acrylamide warhead, 21,22 during which we became interested in dipeptides A and B 23 ( Figure 1) as leads due to their attractive potency and specificity for TG2.…”
mentioning
confidence: 99%
“…In contrast, constitutive TG2 overexpression in B6 mouse neurons (Tucholski et al 2006) did not modify disease onset or progression in R6/2 on a B6 background (R6/2B) (Kumar et al 2012). Nor did genetic deletion of TG2 [ (Nanda et al 2001) backcrossed 12 generations to B6] in two different HD models, where experiments were performed according to the recommended guidelines for animal husbandry and study design (Menalled et al 2014b), calling into question the role of TG2 in HD.…”
Section: Cell Adhesion and Spreadingmentioning
confidence: 99%